Quantitative Easing Impact on the Global Economy - Małecki, Jakub (Wpływ luzowania ilościowego na globalną gospodarkę, 2023)
The article represents an attempt to evaluate the role of Quantitative Easing (QE) in the economy. The analysis of past events involving monetary policy serves as the basis for forming an opinion on the broader impact of QE on the economic and financial system. The substantive content, particularly the beginning, aims to provide an understanding of the monetary system and the fundamental actions undertaken by the central banks. The research component delves into the global financial crisis of 2007-2008 and the period of the coronavirus pandemic. Description of the decisions in monetary policy, which took place over more than a 15-year period, thoroughly covers the actions of three central banks: the Bank of Japan, the US Federal Reserve, and the European Central Bank. Statistical data, researcher opinions, academic papers, and press content are gathered to showcase implementation of specific intervention measures, what tendencies were observable and how they impacted the economy.
Małecki, J. (2023). Quantitative Easing Impact on the Global Economy. In A. Kuźmińska-Haberla, S. Bobowski (Eds.), Ekonomia i międzynarodowe stosunki gospodarcze (pp. 9-23). Wroclaw University of Economic and Business
Keywords: quantitative easing; monetary policy; central banks; financial markets; crisis; luzowanie ilościowe; polityka pieniężna; banki centralne; rynki finansowe; kryzys